Formulation and validation of mathematical model for co-sputtering conditions to attain stoichiometric CZTS films: Expedience of using all metal sulfide targets - Munira Sultana; Afrina Sharmin; Md Rashed Alam; Shahran Ahmed; Md Aftab Ali Shaikh; M.S. Bashar (Heliyon)
A soda lime glass substrate is used for fabricating Cu2ZnSnS4 (CZTS) thin films using copper (II) sulfide (CuS), zinc sulfide (ZnS), and tin sulfide (SnS) targets using an advanced co-sputtering deposition process. Following that, the films are annealed at 470 °C without sulfur (S). An algorithm based on the deposition rate of the previously specified targets set the co-sputtering condition, which maintains a deposition pressure of 5, 10, 15, and 20 mTorr. When studied at different deposition pressures, carrier concentration, resistivity, band gap, and crystallite size show significant correlations. The systematic variation of deposition pressure (5–20 mTorr) shows a constant increase in crystallite size. Resistivity decreases with pressure, but the band gap rises. The film has the highest resistivity at 5 mTorr Argon (Ar) deposition pressure and the highest carrier concentration at 10 mTorr. The EDX study shows that annealed films have a good stoichiometric ratio without sulfurization. Stoichiometry control, energy economy, and process simplicity improve when sulfurization is skipped for CZTS manufacturing. The findings explain correlations according to the intended use, thus experimentalists in this field will be interested in them.